Establishing a common vocabulary of key concepts for the effective ımplementation of applied behavior analysis - Traci M Cihon; Joseph H Cihon; Guy M. Bedient (International Electronic Journal of Elementary Education, 2016)
The technical language of behavior analysis is arguably necessary to share ideas and research with precision among each other. However, it can hinder effective implementation of behavior analytic techniques when it prevents clear communication between the supervising behavior analyst and behavior technicians. The present paper provides a case example of the development of a shared vocabulary, using plain English when possible, among supervisors and supervisees at a large public school district in which behavior analytic services were provided for children diagnosed with autism spectrum disorders. A list of terms and definitions are provided as well as suggestions on how to develop shared vocabularies within the readers’ own service provision context.